Adsorption and reaction pathways of a chiral probe molecule, S-glycidol on a Pd(111) surface. Issue 2 (16th October 2014) - Mahapatra, Mausumi; Tysoe, Wilfred T.
Abstract : The chemistry of S -glycidol is studied on a Pd(111) surface using temperature-programmed desorption and reflection–absorption infrared spectroscopy to explore its suitability as a chiral probe molecule and to follow its reaction pathway. Abstract : The chemistry of S -glycidol is studied on a Pd(111) surface using temperature-programmed desorption and reflection–absorption infrared spectroscopy to explore its suitability as a chiral probe molecule and to follow its reaction pathway. It is found that the majority of the S -glycidol desorbs intact with less than 8% decomposing. Decomposition is initiated by forming an S -glycidate intermediate below 200 K and this further reacts via C–O scission of the epoxy ring. This reaction is controlled by the stability of the carbocation intermediate to preferentially form an ethoxy aldehyde intermediate that thermally decomposes to desorb carbon monoxide, hydrogen and ethanol.